The relevance of linguistic and professional knowledge as contributing factors for technical translation in the area of aircraft (maintenance). - Terenzi, Daniela; Pizzi, Maria Claudia Bontempi (The ESPecialist, 2020)
For security reasons, quantity and constant updates, it is impracticable to translate documents related to the operation and maintenance of aircraft. However, most professionals in this field are not native English speakers and are in contact with this English written documentation on a daily basis so they can do their job. Therefore, it is important that aviation professionals have materials of reference, especially for technical terms, that are reliable sources of information. However, in addition to the lack of this type of material, there is a challenge for its development. The objective of this article is, based on theoretical references and examples from the practice of researching and teaching English for specific purposes, to encourage the discussion about the teamwork of the language teacher and the professional of aircraft maintenance in the production of reference materials, such as technical glossaries. Based on the arguments presented, it is concluded that this partnership has benefits for both areas, languages and technical.